Effects of a Mediterranean diet on blood pressure: a systematic review and meta-analysis of randomized controlled trials and observational studies. Issue 4 (14th April 2021) - Cowell, Owen R.; Mistry, Nathan; Deighton, Kevin; Matu, Jamie; Griffiths, Alex; Minihane, Anne Marie; Mathers, John C.; Shannon, Oliver M.; Siervo, Mario
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To conduct a systematic review and meta-analysis investigating effects of MedDiet on blood pressure in randomized controlled trials (RCTs) and associations of MedDiet with risk of hypertension in observational studies. Methods: PubMed, The Cochrane Library and EBSCOhost were searched from inception until January 2020 for studies that met the following criteria: participants aged at least 18 years, RCTs investigating effects of a MedDiet versus control on BP, observational studies exploring associations between MedDiet adherence and risk of hypertension. Random-effects meta-analyses were conducted. Meta-regression and subgroup analyses were performed for RCTs to identify potential effect moderators. Results: Nineteen RCTs reporting data on 4137 participants and 16 observational studies reporting data on 59 001 participants were included in the meta-analysis. MedDiet interventions reduced SBP and DBP by a mean −1.4 mmHg (95% CI: −2.40 to −0.39 mmHg, P  = 0.007, I 2  = 53.5%, Q  = 44.7, τ 2  = 1.65, df = 19) and −1.5 mmHg (95% CI: −2.74 to −0.32 mmHg, P  = 0.013, I 2  = 71.5%, Q  = 51.6, τ 2  = 4.72, df  = 19) versus control, respectively. Meta-regression revealed that longer study duration and higher baseline SBP was associated with a greater decrease in BP, in response to a MedDiet ( P  < 0.05). In observational studies, odds of developing hypertension were 13% lower with higher versus lower MedDiet adherence (95% CI: 0.78--0.98, P  = 0.017, I 2  = 69.6%, Q  = 41.1, τ 2  = 0.03, df  = 17). Conclusion: Data suggest that MedDiet is an effective dietary strategy to aid BP control, which may contribute towards the lower risk of CVD reported with this dietary pattern. This study was registered with PROSPERO: CRD42019125073.